Proposal of a concept of metaphilosophy - Ortega Monge, Guillermo (2025)
This article studies the recent notions of metaphilosophy and, after adopting one of them (metaphilosophy as thinking about philosophy), attempts to propose a conception of philosophy as an object of study itself and intends to organize the contents of metaphilosophy